Diversity-triggered deterministic bacterial assembly constrains community functions - Weibing Xun (Nature Portfolio, 2019)
The role of microbial β-diversity in soil ecosystem function is not well-studied. Here, the authors use genetic data to show that microbial α-diversity levels may have impacts on stochastic/deterministic assembly processes and functions of soil microbiome.